The Development of Mathematics Learning Tools to Improve High School Students' Critical Thinking Abilities - Nurhayati; Maria F V Ruslau; Irmawaty Natsir; Rian Ade Pratama; Henie Poerwandar Asmaningrum (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
This research aims to produce high school mathematics learning tools to improve students' critical thinking skills which include Student Worksheets (LKPD), and learning outcome assessment test sheets that are valid, practical and effective. The combination of learning methods and technological devices provides a fun learning process and helps students improve their critical thinking skills so as to provide benefits to students' learning outcomes. The type of research carried out is the research and development method. The development model referred to is using a 4-D development model which consists of four stages, namely the define stage, the design stage, the develop stage and the disseminate stage. The research instruments used were validation sheets, teacher practicality sheets, student practicality sheets, learning implementation observation sheets, and test sheets. The research data obtained that the level of device validity was in the valid category with an average score of 74.5. The teacher obtained a score of 60.5 for practicality and 61.88 for student practicality, so that the product met the practical category, and the results of students' mathematics learning achievement tests in the field trial showed that 83.3% of students had achieved the Minimum Completeness Criteria (KKM) so that the product The worksheet meets the effective category. Based on the obtained validity, practicality and effectiveness figures, it can be concluded that the learning tools developed are suitable for use in the classroom learning process.